Soil morphological properties related to Páramo ecosystems in Nariño, Southern Colombia - Zúñiga Ugalde, Felipe; Huertas Delgado, Jenny; Guerrero Obando, Gabriela; Dörner Fernández, José; Sarasty Bravo, Jairo; Burbano Orjuela, Hernán (REVISTA TERRA LATINOAMERICANA, 2018)
Franklin Delano Roosevelt (1882-1945) stated: “A nation that destroys its soils destroys itself.” How can we get the soil closer to society so that this sentence does not become reality? One alternative is to develop didactic tools that allow socializing the information that soil profiles can provide. Soil morphological properties associated with páramo ecosystems and their link with ecosystem services (SE) were studied in Nariño, Southern Colombia through a pedotransference function (FPTs) with an instructive approach, oriented to the environmental regulation of the study area. Forty-two soil horizons were described morphologically in a range of 9 ecosystems (páramos to crops). In general, the deepest soils are found in páramos and native forest systems. These soils are also dark, evidence of accumulation of soil organic carbon. Soil bulk density varied between 0.13 and 1.35 Mg m-3, and soil organic carbon ranged between 0.60 and 23.77%. This property explains soil bulk density (P < 0.0001; r2 = 0.83) and is described by an inverse first order equation. Soil organic carbon is a useful indicator to estimate quantitative aspects of the soil pore system and to infer the ecosystem services of water, air and nutrient regulation of the páramos. Finally, “Land information cards” are proposed as tools to will inform and raise awareness of the society regarding the importance of the soil as natural capital and prevent the sentence of F.D. Roosevelt from becoming an uncomfortable reality.